Comparing Farmers Capacity in Dealing with Huanglongbing Disease (A Case Study in Jember Regency) - Zain, Hanita Athasari; Wastutiningsih, Sri Peni; Subejo, Subejo (Agro Ekonomi, 2025)
Jember Regency is included in top three regencies in Province of East Java that have the largest amount of Siamese citrus production, with a total of 116.473,5 tons which shows a decrease from previous year, that is 171.322,3 tons on 2021. There are two subdistricts in Jember Regency that become Siamese citrus centre, namely Semboro Subdistrict and Umbulsari Subdistrict. Semboro Subdistrict has a smaller land area of Siamese citrus than Umbulsari Subdistrict, but it has more productivity that reached up to 28 ton/ha. It is assumed that the intensity of Huanglongbing (HLB) disease and how farmers overcome the disease may cause the difference. HLB is an infectious disease caused by Liberibacter asiaticus and transmitted by citrus psyllid vector insect. Until now, there is no specific best treatment has been found for citrus crops affected by HLB disease. Thus, this research aims to measure and compare the farmers’ capacity level in overcoming HLB disease with Andragogy Theory as the used grand theory. After conducting a proportional random sampling, data of 30 farmers from Semboro Subdistrict and 32 farmers from Umbulsari Subdistrict were analyzed by independent sample t-test. The result shows there is no significant difference between farmers’ capacity level in Umbulsari and Semboro Subdistrict. The capacity level of farmers in Umbulsari Subdistrict is 62,33%, meanwhile in Semboro Subdistrict is 63,27%.